Postcard from Georg Bredig to Max Bredig, July 21, 1937 - Bredig, Georg (1937)
Georg Bredig (1868-1944) informs his son, Max Bredig (1902-1977), that he forwarded a letter from Kasimir Fajans (1887-1975). He also provides a brief update on family matters.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Third Reich; Fajans, Kasimir, 1887-1975